Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the system of equations:
[tex]\[ \left\{ \begin{array}{c} 3y = 4x + 7 \\ -4x - 4y = 28 \end{array} \right. \][/tex]
we will substitute solutions into the equations to verify them.
## Step-by-Step Solution:
### Step 1: Write down the equations in the system:
[tex]\[ \begin{array}{l} 3y = 4x + 7 \quad \text{(Equation 1)} \\ -4x - 4y = 28 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 2: Solve one of the equations for one variable:
Let's isolate [tex]\( y \)[/tex] in Equation 1:
[tex]\[ 3y = 4x + 7 \][/tex]
[tex]\[ y = \frac{4x + 7}{3} \][/tex]
### Step 3: Substitute the expression for [tex]\( y \)[/tex] into Equation 2:
Substitute [tex]\( y = \frac{4x + 7}{3} \)[/tex] into Equation 2:
[tex]\[ -4x - 4 \left(\frac{4x + 7}{3}\right) = 28 \][/tex]
### Step 4: Clear the fraction by multiplying through by 3:
[tex]\[ -12x - 4(4x + 7) = 84 \][/tex]
[tex]\[ -12x - 16x - 28 = 84 \][/tex]
### Step 5: Combine like terms:
[tex]\[ -28x - 28 = 84 \][/tex]
### Step 6: Solve for [tex]\( x \)[/tex]:
First, add 28 to both sides:
[tex]\[ -28x - 28 + 28 = 84 + 28 \][/tex]
[tex]\[ -28x = 112 \][/tex]
Next, divide by [tex]\(-28\)[/tex]:
[tex]\[ x = \frac{112}{-28} \][/tex]
[tex]\[ x = -4 \][/tex]
### Step 7: Substitute [tex]\( x = -4 \)[/tex] back into the expression we found for [tex]\( y \)[/tex]:
Recall [tex]\( y = \frac{4x + 7}{3} \)[/tex]:
[tex]\[ y = \frac{4(-4) + 7}{3} \][/tex]
[tex]\[ y = \frac{-16 + 7}{3} \][/tex]
[tex]\[ y = \frac{-9}{3} \][/tex]
[tex]\[ y = -3 \][/tex]
### Step 8: Write down the solution:
The solution to the system of equations is:
[tex]\[ x = -4, \quad y = -3 \][/tex]
### Step 9: Verify the solution:
Substitute [tex]\( x = -4 \)[/tex] and [tex]\( y = -3 \)[/tex] back into the original equations to check.
For [tex]\( 3y = 4x + 7 \)[/tex]:
[tex]\[ 3(-3) = 4(-4) + 7 \][/tex]
[tex]\[ -9 = -16 + 7 \][/tex]
[tex]\[ -9 = -9 \quad \text{(True)} \][/tex]
For [tex]\( -4x - 4y = 28 \)[/tex]:
[tex]\[ -4(-4) - 4(-3) = 28 \][/tex]
[tex]\[ 16 + 12 = 28 \][/tex]
[tex]\[ 28 = 28 \quad \text{(True)} \][/tex]
Since both equations are satisfied, the solution is correct. Therefore, the solution to the system of equations is:
[tex]\[ \boxed{x = -4, y = -3} \][/tex]
[tex]\[ \left\{ \begin{array}{c} 3y = 4x + 7 \\ -4x - 4y = 28 \end{array} \right. \][/tex]
we will substitute solutions into the equations to verify them.
## Step-by-Step Solution:
### Step 1: Write down the equations in the system:
[tex]\[ \begin{array}{l} 3y = 4x + 7 \quad \text{(Equation 1)} \\ -4x - 4y = 28 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 2: Solve one of the equations for one variable:
Let's isolate [tex]\( y \)[/tex] in Equation 1:
[tex]\[ 3y = 4x + 7 \][/tex]
[tex]\[ y = \frac{4x + 7}{3} \][/tex]
### Step 3: Substitute the expression for [tex]\( y \)[/tex] into Equation 2:
Substitute [tex]\( y = \frac{4x + 7}{3} \)[/tex] into Equation 2:
[tex]\[ -4x - 4 \left(\frac{4x + 7}{3}\right) = 28 \][/tex]
### Step 4: Clear the fraction by multiplying through by 3:
[tex]\[ -12x - 4(4x + 7) = 84 \][/tex]
[tex]\[ -12x - 16x - 28 = 84 \][/tex]
### Step 5: Combine like terms:
[tex]\[ -28x - 28 = 84 \][/tex]
### Step 6: Solve for [tex]\( x \)[/tex]:
First, add 28 to both sides:
[tex]\[ -28x - 28 + 28 = 84 + 28 \][/tex]
[tex]\[ -28x = 112 \][/tex]
Next, divide by [tex]\(-28\)[/tex]:
[tex]\[ x = \frac{112}{-28} \][/tex]
[tex]\[ x = -4 \][/tex]
### Step 7: Substitute [tex]\( x = -4 \)[/tex] back into the expression we found for [tex]\( y \)[/tex]:
Recall [tex]\( y = \frac{4x + 7}{3} \)[/tex]:
[tex]\[ y = \frac{4(-4) + 7}{3} \][/tex]
[tex]\[ y = \frac{-16 + 7}{3} \][/tex]
[tex]\[ y = \frac{-9}{3} \][/tex]
[tex]\[ y = -3 \][/tex]
### Step 8: Write down the solution:
The solution to the system of equations is:
[tex]\[ x = -4, \quad y = -3 \][/tex]
### Step 9: Verify the solution:
Substitute [tex]\( x = -4 \)[/tex] and [tex]\( y = -3 \)[/tex] back into the original equations to check.
For [tex]\( 3y = 4x + 7 \)[/tex]:
[tex]\[ 3(-3) = 4(-4) + 7 \][/tex]
[tex]\[ -9 = -16 + 7 \][/tex]
[tex]\[ -9 = -9 \quad \text{(True)} \][/tex]
For [tex]\( -4x - 4y = 28 \)[/tex]:
[tex]\[ -4(-4) - 4(-3) = 28 \][/tex]
[tex]\[ 16 + 12 = 28 \][/tex]
[tex]\[ 28 = 28 \quad \text{(True)} \][/tex]
Since both equations are satisfied, the solution is correct. Therefore, the solution to the system of equations is:
[tex]\[ \boxed{x = -4, y = -3} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.